206k views
2 votes
Solve the exponential equation by rewriting the base. explain the steps towards your answer.


((1)/(9) )^(2n) =27^(n)

2 Answers

3 votes

Answer:

n=0

Explanation:

Given in the question an equation


(1)/(9)^(2n)=27^(n)

we can write


(1)/(9)

as


((1)/(3))^(2)

further as


3^(-2)

so


3^(-2(2n))=3^(3n)


3^(-4n)=3^(3n)

Since now the base is same

and we know that


x^(n)=x^(m)\\n=m

-4n = 3n

n cancel out which means n =0

User Daemes
by
5.6k points
0 votes

Answer:
n=0

Explanation:

You need to remember that:


a^n=a^m\\n=m

By the Power of a power property:


(a^m)^n=a^(mn)

By the Negative exponent rule:


a^(-1)=(1)/(a)

Therefore, having the expression
((1)/(9) )^(2n)=27^(n):

Descompose 27 and 9 into their prime factors:


27=3*3*3=3^3


9=3*3=3^2

Rewrite the expression and simplify. Then:


(3^(-2))^(2n)=(3^3)^n\\3^(-4n)=3^(3n)\\-4n=3n\\-4n-3n=0\\n=0

User Amir Nissim
by
5.3k points